PERMINTAAN BUAH-BUAHAN RUMAHTANGGA DI PROPINSI LAMPUNG - Rini Desfaryani; Sri Hartoyo; Lukytawati Anggraeni (Departmen of Agribusiness, Economics and Management Faculty, Bogor Agricultural University, 2016)
One of commodity which is important to be fulfilled is fruit. From producer side, it has been available much in Lampung Province but has not been utilized optimally by consumer. This study purposed to analyze the factors influencing fruit demand and the response of demand changes due to shifting of price and income. The analysis was conducted by using AIDS (Almost Ideal Demand System) model and the parameter was estimated by using SUR (Seemingly Unrelated Regression) method. The results stated that the fruit demand was influenced by the fruit price (either own-price or cross-price), expenditure, and the number of household members. The elasticity shows that the own-price for all kinds of fruit is inelastic. The cross-price elasticity indicates that there are some fruits that have substitution or complementary relationship among them and in all types of fruits, income elasticity has positive sign.